Impact of Patient Beliefs on Blood Pressure Control in the General Population: Findings from the Population-Based STAAB Cohort Study - Theresa Tiffe; Caroline Morbach; Viktoria Rücker; Götz Gelbrich; Martin Wagner; Hermann Faller; Stefan Störk; Peter U. Heuschmann (International Journal of Hypertension)
Background. Effective antihypertensive treatment depends on patient compliance regarding prescribed medications. We assessed the impact of beliefs related towards antihypertensive medication on blood pressure control in a population-based sample treated for hypertension. Methods. We used data from the Characteristics and Course of Heart Failure Stages A-B and Determinants of Progression (STAAB) study investigating 5000 inhabitants aged 30 to 79 years from the general population of Würzburg, Germany. The Beliefs about Medicines Questionnaire German Version (BMQ-D) was provided in a subsample without established cardiovascular diseases (CVD) treated for hypertension. We evaluated the association between inadequately controlled hypertension (systolic RR >140/90 mmHg; >140/85 mmHg in diabetics) and reported concerns about and necessity of antihypertensive medication. Results. Data from 293 participants (49.5% women, median age 64 years [quartiles 56.0; 69.0]) entered the analysis. Despite medication, half of the participants (49.8%) were above the recommended blood pressure target. Stratified for sex, inadequately controlled hypertension was less frequent in women reporting higher levels of concerns (OR 0.36; 95%CI 0.17-0.74), whereas no such association was apparent in men. We found no association for specific-necessity in any model. Conclusion. Beliefs regarding the necessity of prescribed medication did not affect hypertension control. An inverse association between concerns about medication and inappropriately controlled hypertension was found for women only. Our findings highlight that medication-related beliefs constitute a serious barrier of successful implementation of treatment guidelines and underline the role of educational interventions taking into account sex-related differences.